Dark tourism, the dark side of cultural tourism: application to the city of Porto - Liberato, Dália (2019)
Dark Tourism represents an extension of cultural tourism, once it was necessary to innovate this tourism typology justiﬁed by a decrease in demand. This change, was veriﬁed in the tourist experience level, that is, to provide unique moments in the cultural level, through the experience, so that it could be the option for a greater number of tourists in the destination. Dark Tourism sites include concentration camps, inactive prisons, serial killers homes, cemeteries, and all other venues that meet the standards of death, tragedy and suffering (Biran et al. 2011; Braithwaite and Lee 2006; Dunkley et al. 2011; Kang et al. 2012; Light 2016, 2017; Podoshen 2013; Podoshen et al. 2015; Stone and Sharpley 2008, 2009; Stone 2012; Yan et al. 2016; and Zhang et al. 2016). In Portugal there are some sites associated with the practice of Dark Tourism, although this is not yet sufﬁciently explored. The main objective of this investigation is the evaluation of Dark Tourism potential in the city of Porto. Partial objectives are: proving the existence of a market niche in Porto associated to Dark Tourism; understand if the city of Porto has tourism resources and tourism demand, able to develop a tourism experience within the Dark Tourism offer; and to sensitize the Destination Management Organizations (DMO ’ s) in Porto to the opportunity of this market, through 178 questionnaires, applied to tourists/visitors in the city of Porto. This research conﬁrmed some objectives, variables and proposed ﬁelds.